Implementation of Tax Administration Services and its Challenges at KPP Pratama Jakarta Kebon Jeruk Satu: A Review of Field Practices - Rena Renata Melanda; Yananto Mihadi Putra; Ana Farida Sahara (Baca Dulu Publisher, 2025)
This article aims to examine the implementation of tax administration services at the Jakarta Kebon Jeruk Satu Tax Office (KPP Pratama Jakarta) through a literature review approach based on industry experience. The focus of this article covers annual tax return assistance services, the implementation of Business Development Services (BDS), and digital public relations activities. The review indicates that the KPP has implemented various technology-based service strategies and public education to improve taxpayer compliance. However, several obstacles, such as low digital literacy, limited training facilities, and less than optimal reach of social media content, remain challenges in service implementation. This article provides an overview of tax practices in the field and offers several recommendations for future improvements.